Ethnobotanical study of wild edible plants of Kara and Kwego semi-pastoralist people in Lower Omo River Valley, Debub Omo Zone, SNNPR, Ethiopia - Teklehaymanot Tilahun; Giday Mirutse (BMC, 2010)
Abstract Background The rural populations in Ethiopia have a rich knowledge of wild edible plants and consumption of wild edible plants is still an integral part of the different cultures in the country. In the southern part of the country, wild edible plants are used as dietary supplements and a means of survival during times of food shortage. Therefore, the aim of this study is to document the wild edible plants gathered and consumed by Kara and Kwego people, and to analyze patterns of use between the two people. Methods A cross sectional ethnobotanical study of wild edible plant species was conducted from January 2005 to March 2007. About 10% of each people: 150 Kara and 56 Kwego were randomly selected to serve as informants. Data were collected using semi-structured questionnaire and group discussions. Analysis of variance (α = 0.05) was used to test the similarity of species richness of wild edible plants reported by Kara and Kwego people; Pearson's Chi-square test (α = 0.05) was used to test similarity of growth forms and plant parts of wild edible plants used between the two people. Results Thirty-eight wild plant species were reported as food sources that were gathered and consumed both at times of plenty and scarcity; three were unique to Kara, five to Kwego and 14 had similar local names. The plant species were distributed among 23 families and 33 genera. The species richness: families, genera and species (p > 0.05) were not significantly different between Kara and Kwego. Nineteen (50%) of the reported wild edible plants were trees, 11 (29%) were shrubs, six (16%) were herbs and two (5%) were climbers. Forty plant parts were indicated as edible: 23 (58.97%) fruits, 13 (33.33%) leaves, 3 (7.69%) roots and one (2.56%) seed. There was no difference between wild edible plants growth forms reported (Pearson's Chi-square test (d.f. = 3) = 0.872) and plant parts used (Pearson's Chi-square test (d.f. = 3) = 0.994) by Kara and Kwego people. The majority of wild edible plants were gathered and consumed from 'Duka' (March) to 'Halet' (May) and from 'Meko' (August) to 'Tejo' (November). Sixteen (41%) of the plant parts were used as a substitute for cultivated vegetables during times of scarcity. The vegetables were chopped and boiled to make 'Belesha' (sauce) or as a relish to 'Adano' (porridge). The ripe fruits were gathered and consumed fresh and some were made into juices. The seeds and underground parts were only consumed in times of famine. Thirty-seven percent of the wild edible plants were used as medicine and 23.6% were used for other functions. Conclusions The wild edible plants were used as supplements to the cultivated crops and as famine foods between harvesting seasons. But information on the nutritional values and possible toxic effects of most of the wild edible plants reported by Kara and Kwego, and others in different part of Ethiopia is not available. Therefore, the documented information on the wild edible plants may serve as baseline data for future studies on nutritional values and possible side effects, and to identify plants that may improve nutrition and increase dietary diversity. Some of these wild edible plants may have the potential to be valuable food sources (if cultivated) and could be part of a strategy in tackling food insecurity.